The effectiveness of pharmacological and non-pharmacological interventions for fatigue in people living with chronic kidney disease: A protocol for a systematic review - Hannah Mary Louise Young; Lisa Ancliffe; Ffion Curtis; Oluwafemi Efuntoye; Matthew PM Graham-Brown; Selina Lock; Kathrine Parker; Chris Rolfe; Ellesha Smith; Aniebiot-Abasi Udofia; James O Burton; Caroline Booth; et al. (PLoS ONE, 2026)
Chronic kidney disease (CKD) affects approximately 850 million people worldwide and is associated with a substantial and growing symptom burden. Fatigue is one of the most common and debilitating symptoms across all stages of CKD, with prevalence far exceeding that of the general population. It profoundly affects quality of life, daily functioning, and clinical outcomes, underscoring the need to identify and evaluate effective pharmacological and non-pharmacological strategies for its management. This protocol outlines methods for a systematic review to evaluate the efficacy, safety, and perceived effectiveness of interventions for fatigue in people with CKD. We will include randomised controlled trials, non-randomised controlled trials, before-and-after studies, and qualitative evaluations in adults and children with any stage of CKD. Searches will be conducted in MEDLINE, Embase, CINAHL, Web of Science Core Collection, PsycINFO, and ClinicalTrials.gov, alongside grey literature via Google Scholar. No language or publication date restrictions will be applied. Study selection will follow a two-stage screening process, with two reviewers independently assessing titles/abstracts and then full texts using predefined eligibility criteria. Data will be extracted using a standardised form, capturing study characteristics, interventions, and outcomes. Risk of bias will be assessed with the NIH Study Quality Assessment Tools or the Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research. Results will be synthesised narratively, and, where appropriate, pooled using meta-analysis. Certainty of the evidence for the primary outcome will be assessed using the GRADE approach and presented in a Summary of Findings table. This review will provide a comprehensive synthesis of evidence on interventions for fatigue in CKD, highlight gaps to guide future research, and inform the UK Kidney Association Symptom Guidelines.